2018
DOI: 10.1002/chem.201800617
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structures, and Optical Properties of Azahelicene Derivatives and Unexpected Formation of Azahepta[8]circulenes

Abstract: Polycyclic heteroaromatic compounds including pyrrole units are promising functional scaffolds owing to their electron-rich nature, bright fluorescence, and applicability to anion recognition at the pyrrolic hydrogen atom. We report herein the effective synthesis of pseudo-aza[5]helicene and aza[7]helicene derivatives, and unexpected formation of azahepta[8]circulenes by oxidative fusion reactions. By choosing reaction conditions and peripheral substituents attached at the terminal indole moieties, we obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 93 publications
5
45
0
1
Order By: Relevance
“…Scheme 41. Synthesis of trisaza [7]helicenes 163a-c from 164a-c. 177 In 2012, Hiroto, Shinokubo, et al reported the selective oxidative fusion of 2 aminoanthracenes mediated by DDQ to provide pyrazine-fused bisanthracenes together with pyrrole-fused dimer 167a,b obtained as by-products and displaying an aza [5]helicenic structure with a stable helical conformation thanks to the presence of bulky ethynylsilylated groups (Scheme 42). 178 ECD and CPL activity were indeed measured for enantiopure compounds prepared by chiral HPLC resolution over a CHIRALPAK-IA column using ethyl acetate/hexane (1:10) as the eluent.…”
Section: A) B)mentioning
confidence: 99%
“…Scheme 41. Synthesis of trisaza [7]helicenes 163a-c from 164a-c. 177 In 2012, Hiroto, Shinokubo, et al reported the selective oxidative fusion of 2 aminoanthracenes mediated by DDQ to provide pyrazine-fused bisanthracenes together with pyrrole-fused dimer 167a,b obtained as by-products and displaying an aza [5]helicenic structure with a stable helical conformation thanks to the presence of bulky ethynylsilylated groups (Scheme 42). 178 ECD and CPL activity were indeed measured for enantiopure compounds prepared by chiral HPLC resolution over a CHIRALPAK-IA column using ethyl acetate/hexane (1:10) as the eluent.…”
Section: A) B)mentioning
confidence: 99%
“…Here, a macrocycle consisting of four pyrrole rings connected by ortho ‐phenylene moieties was oxidatively contracted to 182 in excellent yield by the action of DDQ and scandium(III) triflate in boiling toluene. Products 183 – 185 were prepared in a similar way . Depending on the conditions and oxidant used, the bis(indolyl)helicene 183 or the closed, nonplanar circulene analogue 184 can be obtained in good yields from the same precursor.…”
Section: Intramolecular Oxidative Aromatic Couplingmentioning
confidence: 99%
“…Products 183-185 were prepared in asimilar way. [191] Depending on the conditions and oxidant used, the bis-(indolyl)helicene 183 or the closed, nonplanar circulene analogue 184 can be obtained in good yields from the same precursor.The eight-membered ring in the latter case readily forms under the same conditions as those used for the synthesis of circulene 182,whereas the preparation of its open form 183 requires the use of much milder conditions (PIFAin CH 2 Cl 2 at À78 8 8C). Thee fficiencyo ft he DDQ/Sc(OTf) 3 system for pyrrole-pyrrole intramolecular oxidative coupling has also been demonstrated by the synthesis of paracyclophane 186,which contains asegregated donor-acceptor-donor system with stacked tetrafluorobenzene rings as acceptors.…”
Section: Dyes and Heterocyclic Polyarenesmentioning
confidence: 99%
“…Recently, we reported the synthesis of triaza-quasi-[8]circulene 12a, 11 which lacks one heterole moiety from the hetero[8] circulene structure. 12 Due to the structural constraint, 12a takes on a non-planar geometry. Interestingly, under milder conditions, triaza[7]helicene 13a was exclusively obtained from the identical precursor 11a.…”
Section: Introductionmentioning
confidence: 99%